Pengembangan DC Chopper Sebagai Pengontrol Daya Pada Sistem Energi Terbarukan - Dendi Agustian; Melti Septiani; Sohip Romdoni (Jurnal Teknik Mesin, Industri, Elektro dan Informatika, 2024)
Renewable energy systems require effective and efficient power control for men-optimizing electricity production. One of the power control technologies used in renewable energy systems is DC Chopper. DC Chopper is an electronic device used to control the voltage and electric current in the DC system. In this study, the development of DC Chopper as a power controller in the renewable energy system was discussed. This research is to introduce the use of DC Chopper as a power controller in the renewable energy system and to the effect of the use of DC Chopper on the production of the new system. This research is the method of using a delay experiment to test DC Chopper on the solar panel system. The results showed that the use of DC Chopper PANA solar panel system can increase the efficiency of electricity production level 20%. In addition, Chopper DC Rona can increase the reliability and age of the renewable energy system because it can reduce the burden on the system.